A Study of Public Mental Health Status and Group Differences in China in the Post-Epidemic Era - Yuan, Zhitao; Ni, Na; Huang, Shen; Zhao, Li Xin; Cheng, Cheng; Yang, Mengyuan; Wang, Xianyang; Liang, Shuyi; Wu, Shengjun (Journal of Educational Research and Policies, 2025)
Objective: To assess the multidimensional psychological status of the Chinese public In terms of general health status, perceived stress, social support, and psychological resilience in the post-epidemic era, this project intends to take cognition, social support, and psychological resilience as the core and systematically analyze the health status of different groups of people. This study aimed to systematically analyze the health status of different groups of people and provide a scientific basis for the precise intervention of the health of Chinese residents. Methods: Multi-stage convenience sampling was used to collect data through the Questionnaire Star platform combined with offline channels from February to May 2025. Questionnaires were collected from 7997 respondents nationwide using the General Health Questionnaire (GHQ-28), the Perceived Stress Scale (CPSS), the Multidimensional Perceived Social Support Scale (MSPSS), and the Psychological Resilience Scale (CD-RISC-10). Standardized assessment combined with stratified logistic regression was used to explore the influencing factors. Results: A total of 52.2% of the population suffered from mental health problems, 4.3% suffered from serious mental health problems, and the demographic differences were significant. Men’s mental health, psychological resilience, and social support were better than women’s; however, women’s perceived stress was higher. The group directly affected by the epidemic had poorer mental health and lower social support, while the mental health of rural residents was better than that of urban residents. The mental health of graduate students was lower than that of undergraduates, and the mental health of junior high school students was the worst of all groups. The mental health of rural residents is better than that of urban residents; the mental health of graduate students is lower than that of undergraduates; the mental health of junior high school students and below is the worst; and the mental health of divorced groups and service and freelance workers is prominent. Demographic differences were significant: men had better mental health (16.11±12.80), psychological resilience (37.32±10.63), and social support (63.85±17.30) than women (p<0.001), but women had higher perceived stress (39.05±6.93 p<0.001); mental health scores of groups directly affected by the epidemic (19.97±13.93 p<0.001); and mental health scores of groups directly affected by the epidemic (19.97±13.63 p<0.001). (19.97±13.73) were significantly higher than those of the unaffected group (13.61±11.23, p<0.001), and social support was lower (62.09±16.51 vs. 64.85±17.88, p<0.001); the mental health of the rural population was better than that of the urban (15.35±12.20; 19.35±13.71, p <0.001); the mental health of graduate students was 25.6% lower than that of undergraduates (25.05±12.18; 19.94±13.57, p<0.001); the group with junior high school education and below had the worst mental health; and the mental health of divorced people and those in the service industry and freelance professions was prominent. Conclusion: This study reveals the complex association between demographic variables and mental health, especially the need to pay attention to the psychological risk of highly educated youth, the reconstruction of social support for graduate students and divorced people, the development of group counseling for stress management for women, the establishment of the “academic-psychological dual tutoring system” for graduate students, the establishment of a community-based emotional support network for divorced people, and the establishment of a community-based emotional support network for urban residents to optimize the accessibility of social resources. The results will provide an important scientific basis for promoting precise and differentiated mental health development in China.